2017
DOI: 10.1164/rccm.201703-0554oc
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Infant Respiratory Microbiota, Environmental Drivers, and Health Consequences. A Prospective Cohort Study

Abstract: Our results suggest that environmental drivers impact microbiota development and, consequently, resistance against development of RTIs. This supports the idea that microbiota form the mediator between early-life environmental risk factors for and susceptibility to RTIs over the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
349
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(388 citation statements)
references
References 32 publications
31
349
5
3
Order By: Relevance
“…In a cohort of 234 Australian infants with a high risk of atopy, Teo and colleagues reported that early Moraxella -dominant nasopharyngeal microbiota was associated with an earlier first upper respiratory infection 11. Similarly, in a cohort of 112 children in the Netherlands, Bosch and colleagues reported an association between enrichment of Moraxella in early life in children and a high frequency of ARIs during the first year of life 9. In contrast, in an analysis of trial data in the Netherlands (n=60), Biesbroek and colleagues found that infants with Moraxella -dominant nasopharyngeal microbiota had a lower risk of subsequent ARI 7.…”
Section: Discussionmentioning
confidence: 96%
“…In a cohort of 234 Australian infants with a high risk of atopy, Teo and colleagues reported that early Moraxella -dominant nasopharyngeal microbiota was associated with an earlier first upper respiratory infection 11. Similarly, in a cohort of 112 children in the Netherlands, Bosch and colleagues reported an association between enrichment of Moraxella in early life in children and a high frequency of ARIs during the first year of life 9. In contrast, in an analysis of trial data in the Netherlands (n=60), Biesbroek and colleagues found that infants with Moraxella -dominant nasopharyngeal microbiota had a lower risk of subsequent ARI 7.…”
Section: Discussionmentioning
confidence: 96%
“…16S-rRNA sequencing. Amplicon libraries of the 16S-rRNA gene (V4 region) were generated, and sequencing was executed as previously described 7 . Amplicon pools were paired-end sequenced in seven runs using an Illumina MiSeq instrument (Illumina Inc., San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Staphylococcus epidermidis (2) Corynebacterium propinquum (3) Dolosigranulum (4) Moraxella (6) Streptococcus (7) Peptoniphilus (5) Finegoldia (8) Haemophilus (9) Fusobacterium (10)…”
Section: Corynebacterium (1)unclassified
See 1 more Smart Citation
“…Variation in community composition has been observed in chronic lung diseases,6 7 and particular micro-organisms or combinations of organisms in infants have been associated with future disease development. Thus deviation from a healthy microbiota in early life appears to play an important role in disease development, with changes evident by 1 week of age 8. The dynamics of the infant airway microbiota and its relationship to disease development has therefore been the focus of increasing attention.…”
mentioning
confidence: 99%